RELATIONSHIP OF STRATEGY AND MILITARYECONOMY IN MODERN CONDITIONS - Khashimov F. B. (Journals Park Publishing, 2023)
The article examines the relationship between war and the economy, the state has a decisive influence on the course of social progress and determines its development, no matter how strongly political and other factors of the Republic of Uzbekistan influence.
Keywords: economic support, military economy, strategy, nonmilitary measures, military-economic potential, economic struggle.